Exploring the Efficiency of Leading and Lagging Indicators in Algorithmic Trading - Vikrant Arora; Sudhanshu Marudgan; Anoushka Ramankulath; Punya Arora; Aditya Kasar (International Journal of Algorithms Design and Analysis Review, 2024)
This paper details a comparison of the overall performance of leading and lagging technical indicators used in algorithmic trading over an extended period. While much of the prior research focuses on index price forecasting and some on statistical arbitrage derived from these predictive techniques, there is a scarcity of studies that assess and evaluate trading strategies. The strategies considered for the study were tested on historical data of the 50 stocks constituting the NIFTYMIDCAP50 index, listed on the National Stock Exchange of India from January 2019 to January 2024. The study examined the Relative Strength Index (RSI), stochastic oscillator, simple moving average (SMA), and exponential moving average (EMA), representing two leading and two lagging indicators, to generate trading signals using fixed parameter sets. Over five years, it was found that strategies based on leading indicators generally underperformed compared to those based on lagging indicators in longer timeframes. The mean percentage returns for strategies using lagging indicators were 37.06, while those using leading indicators were 18.67. The difference in mean returns between leading and lagging indicators across all selected stocks was statistically significant, with a p-value of less than 0.05002.
Keywords: Indian stock market; RSI; Technical analysis; algorithmic trading; algorithms; stochastic oscillator; technical indicators